TRUST AND VALUES OF CONSUMERS IN THE INNOVATION SYSTEM OF RELATIONSHIP MARKETING - Babukh, Ilona; Nikiforov, Petro (Economics and Finance, 2018)
It is emphasized that the traditional model of marketing in modern conditions on oversaturated markets has lost its relevance and was replaced by relation marketing in the 2000s, which, in order to fully meet modern requirements should include elements of other marketing and marketing innovations. A whole range of marketing innovations can be singled out (network marketing, related marketing, retromarketing, etc.), while considering the relationship marketing as a business philosophy is not possible to do without the influence of trust and consumer values in the implementation of these innovations. The phenomenon of trust is analyzed as a moral and ethical problem, as well as a conceptual approach of the marketing of trust in the composition of relationship marketing. It is emphasized that the development of the theory of relationship marketing through trust and the values of consumers will provide business and its customers with an effective tool not only in developing a traditional marketing mix, but also in determining the norms of social exchange based on moral and ethical criteria and raising the business reputation of the enterprise.
Keywords: marketing theory; relationship marketing; marketing innovations; hedonistic and functional consumption; trust; consumer values; marketing of trust; trust factors; business reputation